DEVELOPMENT OF MATHEMATICAL PROBLEMS MODELS OF PISA CONTEXT OCCUPATION FOR STUDENT JUNIOR HIGH SCHOOL - Handayani, Marweny; Putri, Ratu Ilma Indra; Somakim, Somakim (Sriwijaya University Learning and Education International Conference, 2018)
Resolving math problems PISA can assist students in training students' mathematical skills. This aims research to (1) Generate math problems of PISA type work context for valid and practical junior high school students, (2) Knowing the potential effects of mathematics on PISA type of work context on the mathematics ability of junior high school students. The method in this research is research method design research with type development studies consists of two stages namely preliminary or preparation and stage prototiping (formative evaluation) which cover self evaluation, expert reviews and oneto- one, small group, and field test. This research involves 2 mathematicians and students of the class VII SMP Negeri 5 Pangkalpinang. Data collection techniques used are walkthrough, documentation, questionnaires, test results, and interviews. This research produces 10 device type problem PISA context occupation on the material SMP that is valid and practical, as well as having a potential effect on students' mathematical abilities. Kevalidan problem based on expert comments (expert review) and test of empirical validity and reliability test , as well as subject comments one-to-one. On test small group obtained data about practicality problem, and phase field test obtained data on potential effects on students' mathematical abilities that students appear when working on questions. The results of the problem analysis reveal some of the students' difficulties in doing the questions seen from mathematical skills include communication skills, mathematization, representation, reasoning and argumentation, problem-solving strategies, and the ability to use symbolic or language formal.